ANALISIS KURIKULUM DI SEKOLAH MENENGAH PERTAMA (STUDI KASUS DI SMP NEGERI 1 SIAK HULU, KAMPAR) - Dinelti Fitria; Nurhizrah Gitituati; Alwen Bentri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This research is analytical to describe the implementation of the 2013 curriculum at SMP Negeri 1 Siak Hulu and the strengths and weaknesses of implementing the 2013 curriculum at the school. This research is analytical research using descriptive qualitative research. The subjects of this study involved school principals, curriculum representatives, and science teachers at SMP Negeri 1 Siak Hulu. Data and information were obtained from the interviews, observations, and utilization of documents. From the results of the research conducted, it can be concluded that schools have tried their best and were able to implement the 2013 curriculum during the Covid-19 pandemic following predetermined rules. All students continue to receive education and learning services from schools; learning activities during the Covid-19 emergency involve all school stakeholders, parents, students, and the surrounding environment. There are several advantages and disadvantages to the implementation of the curriculum. The advantages and disadvantages of implementing this curriculum must be the subject of further attention and consideration from education policymakers. The curriculum owned by SMP Negeri 1 Siak Hulu can be a guideline for managing education holistically and consistently.